Prefrontal cortex and executive function in young children: a review of NIRS studies - Moriguchi, Yusuke; Hiraki, Kazuo (Frontiers in Human Neuroscience, 2013)
Executive function (EF) refers to the higher-order cognitive control process for the attainment of a specific goal. There are several subcomponents of EF, such as inhibition, cognitive shifting, and working memory. Extensive neuroimaging research in adults has revealed that the lateral prefrontal cortex plays an important role in EF. Developmental studies have reported behavioral evidence showing that EF changes significantly during preschool years. However, the neural mechanism of EF in young children is still unclear. This article reviews recent near-infrared spectroscopy (NIRS) research that examined the relationship between the development of EF and the lateral prefrontal cortex. Specifically, this review focuses on inhibitory control, cognitive shifting, and working memory in young children. Research has consistently shown significant prefrontal activation during tasks in typically developed children, but this activation may be abnormal in children with developmental disorders. Finally, methodological issues and future directions are discussed.